Konsep Pembinaan Warga Binaan Pemasyarakatan Analysis Of Prisoners Guidance To Reduce Level - Marsudi Utoyo (Law Faculty of Universitas Bandar Lampung, 2015)
Correctional systems in addition to aiming to restore correctional inmates as a good citizen, also aims to protect the public against the possibility of repeated criminal acts by prisoners.The problem in this is how the pattern formation is done by the Penitentiary. The method used in this study is through normative approaches. Secondary data was obtained through library and conducted data analysis by means of qualitative analysis. Based on the results of this study concluded that the pattern of development undertaken by the Correctional Institution Correctional inmates to reduce recidivism rate among others, through the stages of admission and orientation or introduction, development stage, the stage of assimilation and integration phases are performed both inside prisons and in outside the prison in accordance stages. Advice can be given that prisons can further enhance the ability of human resources at Penitentiary through training